Dietary Fatty Acid Saturation Modulates Sphingosine-1-Phosphate-Mediated Vascular Function - Daniel W. Nuno; Kathryn G. Lamping (Journal of Diabetes Research)
Sphingolipids, modified by dietary fatty acids, are integral components of plasma membrane and caveolae that are also vasoactive compounds. We hypothesized that dietary fatty acid saturation affects vasoconstriction to sphingosine-1-phosphate (S1P) through caveolar regulation of rho kinase. Wild type (WT) and caveolin-1-deficient (cav-1 KO) mice which lack vascular caveolae were fed a low-fat diet (LF), 60% high-saturated fat diet (lard, HF), or 60% fat diet with equal amounts of lard and n-3 polyunsaturated menhaden oil (MO). Weight gain of WT on HF and MO diets was similar while markedly blunted in cav-1 KO. Neither high-fat diet affected the expression of cav-1, rho, or rho kinase in arteries from WT. In cav-1 KO, MO increased the vascular expression of rho but had no effect on rho kinase. HF had no effect on rho or rho kinase expression in cav-1 KO. S1P produced a concentration-dependent constriction of gracilis arteries from WT on LF that was reduced with HF and restored to normal with MO. Constriction to S1P was reduced in cav-1 KO and no longer affected by a high-saturated fat diet. Inhibition of rho kinase which reduced constriction to PE independent of diet in arteries from WT and cav-1 KO only reduced constriction to S1P in arteries from WT fed MO. The data suggest that dietary fatty acids modify vascular responses to S1P by a caveolar-dependent mechanism which is enhanced by dietary n-3 polyunsaturated fats.